The influence of reporting mode on children's cued personal memories. Issue 9 (20th October 2016) - Glynn, Ruth; Salmon, Karen; Jose, Paul
ABSTRACT: The Autobiographical Memory Test (AMT) is widely used in research contexts to measure the extent to which participants (children or adults) report specific or general memories in response to cue words. Recalling fewer specific and more general memories (overgeneral memory) has been shown to be linked to depression in adults, but findings for youth, in particular, are mixed. Different versions of the AMT may be one contributing factor, yet this issue has received little research attention. The current study investigated the influence of reporting mode (written vs. spoken) on the specificity, length, and content of memories provided by 8- to 10-year-old children ( N  = 48). No significant differences were found in the number of specific responses given in the written and spoken modes. On the other hand, the spoken mode elicited longer and more detailed memories, although most content differences were eliminated when memory length was controlled. These findings suggest that different reporting modes can influence the nature of the memories reported, but the absolute differences are relatively small.